2021
DOI: 10.1001/jamainternmed.2021.2348
|View full text |Cite
|
Sign up to set email alerts
|

Social Connectedness Among Medicare Beneficiaries Following the Onset of the COVID-19 Pandemic

Abstract: Social distancing is an effective strategy to limit contagion and mortality from the COVID-19 pandemic. However, these measures may also decrease perceived social connectedness and conversely increase social isolation, states which are associated with psychologic and physiologic morbidity. [1][2][3][4][5] Patients who are elderly or have disabilities are particularly encouraged to practice social distancing given their higher risk of severe COVID-19 infection, but they also have a higher baseline risk for repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Another report demonstrated a significant association between social isolation and mortality, with the increased death rate in adults reaching up to 35% compared to those receiving social support, even after excluding important disease risk factors [ 54 ]. Moreover, the lack of social connectedness has negatively affected vulnerable groups, such as individuals with chronic illnesses (especially cancer) and those without internet or technology access [ 55 ], more than the rest of the population.…”
Section: Covid-19 and Social Distancingmentioning
confidence: 99%
“…Another report demonstrated a significant association between social isolation and mortality, with the increased death rate in adults reaching up to 35% compared to those receiving social support, even after excluding important disease risk factors [ 54 ]. Moreover, the lack of social connectedness has negatively affected vulnerable groups, such as individuals with chronic illnesses (especially cancer) and those without internet or technology access [ 55 ], more than the rest of the population.…”
Section: Covid-19 and Social Distancingmentioning
confidence: 99%
“…The end date of the study was chosen to assure that follow-up through December 2019 was completed before the onset of the COVID-19 pandemic, so that we could assess the relationship between loneliness and study outcomes independent of the increase in loneliness that has occurred during the pandemic. [12][13][14] We identified all KPCO members who completed multiple MTHAs and used data from their two most recent surveys within a 6-18-month period. We excluded members who did not have 12 months of continuous KPCO membership prior to their first MTHA or 12 months of continuous membership after their second MTHA.…”
Section: Participantsmentioning
confidence: 99%
“…Liotta et al (2020) found that socially connected Italian older adults were better protected from the virus than their socially disconnected peers. Another study found that U.S. Medicare recipients who practiced socially distancing were more likely to report feeling socially isolated (Talcott et al 2021). Community elders who were sexual and gender minorities, lived by themselves, or did not have a partner (Steinman et al 2020), were found to be especially vulnerable.…”
Section: Social Connectedness Of Older Adults During Covid-19mentioning
confidence: 99%